Effect of Management Accounting Practices on Organizational Performance of Nepalese Commercial Banks - Mahatman, Tribhuvan (Shahid Kirti Multidisciplinary Journal, 2025)
Management accounting practices (MAPs) encompass tools and techniques like time-driven activity-based costing and budgeting to aid internal decision-making, costing and performance evaluation within organizations. The study aims to identify the empirical studies that investigate the impact of management accounting practices on organizational performance. The study uses a descriptive research design and survey method to examine impact of management accounting practices on organizational performance in Nepalese commercial banks. The data was collected from 7 Nepalese commercial banks through questionnaires. The questionnaires are distributed to branch managers and customers, using convenience sampling. The study analyzed the responses from 350 branch managers out of 1763 and 392 customers, with 345 being usable data. The banks are selected on the basis of stratified sampling method. The findings were presented using various statistical tools. The study used SPSS V-25 software to analyze primary data, generating descriptive and inferential statistics. The hypothesis was tested using regression analysis. The results showed a positive impact of management accounting practices on organizational performance. The study suggests that Nepalese commercial banks should adopt robust management accounting practices improve their performance. The integration of sustainable practices of management accounting can benefit both banks and their economic growth.